Computer education of information specialists - Miežinienė, Ala (Information & Media, 1994)
The article deals with the problem of library and informology students’ computer education in Vilnius University. Main attitudes, principles and stages of this process are described. The article consists of 5 parts. They discuss the following questions: Development of computers and library education. Computer education of information specialists in Lithuania. Computer education of librarianship and bibliography speciality students in Vilnius University. Characteristics of data bases created for Methodical Library management and library education. Computerization of Methodical Library in the Faculty of Communication.